Analisis Rasio Profitabilitas Terhadap Harga Saham Emiten Kesehatan Pada Daftar Efek Syariah (DES) Periode 2016-2020 - Evi Kurniati; Versiandika Yudha Pratama (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2022)
This study aims to determine the effect of ROA, ROE, NPM and EPS on stock prices of health issuers on the Sharia Securities List for the 2016-2020 period. This research is classified as quantitative research. The data collection method in this study is through secondary data using the company's financial statements. The sample selection technique used purposive sampling method and obtained a number of 8 health sector companies as research samples. The data analysis technique used is multiple linear regression analysis with hypothesis testing including t test and F test. The results show that the ROA, ROE, NPM and EPS partially have no effect and not significant on stock prices. Meanwhile, the simultaneous test shows that the ROA, ROE, NPM and EPS variables have a significant effect on stock prices of health issuers on the Sharia Securities List  for the 2016-2020 period.